Detection of synergistic interactions of polyvinyl alcohol–cassava starch blends through DSC - Lee, Tin Sin (2010)
The synergistic interaction of polyvinyl alcohol (PVOH) and cassava starch was studied by differential scanning calorimetry (DSC) method. Film of the PVOH–cassava starch blends were prepared by solution cast method. Originally, cassava starch film did not show presence of any endothermic peaks in DSC thermogram. However, after adding PVOH to cassava starch, the PVOH–cassava starch blend films showed obvious endothermic peaks with onset and end-point temperatures higher than neat PVOH film. In addition, the PVOH–cassava starch blends have experimental enthalpy of melting higher than theoretical values. This evidence shows that the interactions between PVOH and cassava starch molecules are extensively strong. Due to the synergistic interactions of PVOH and cassava starch, it is postulated that incorporation of 65–75 wt.% of PVOH in cassava starch blend has physical bonding equivalent to neat PVOH